Are There Lessons For Africa From China's Success Against Poverty? - Ravallion, Martin, 1952- 1952- (The World Bank, 2008)
At the outset of China's reform period, the country had a far higher poverty rate than for Africa as a whole. Within five years that was no longer true. This paper tries to explain how China escaped from a situation in which extreme poverty persisted due to failed and unpopular policies. While acknowledging that Africa faces constraints that China did not, and that context matters, two lessons stand out. The first is the importance of productivity growth in smallholder agriculture, which will require both market-based incentives and public support. The second is the role played by strong leadership and a capable public administration at all levels of government